Diagnostic features of type II fibrinoid leukodystrophy (Alexander disease) in a juvenile Beagle dog. (17th February 2023) - Vandenberghe, Hélène; Baiker, Kerstin; Nye, George; Escauriaza, Leticia; Roberts, Emma; Granger, Nicolas; Reeve, Lizzie
Abstract: A 3‐month‐old female entire Beagle presented with a progressive history of caudotentorial encephalopathy. Reactive encephalopathies were ruled out and tests for the most common infectious diseases agents were negative. Magnetic resonance imaging of the brain using a 1.5 Tesla scanner showed diffuse, bilateral, T2‐weighted and T2‐weighted‐FLAIR hyperintense, T1‐weighted hypointense, noncontrast‐enhancing lesions involving the white matter of the cerebellum, brainstem, spinal cord, and forebrain to a lesser extent. There was cerebellar enlargement. Abnormalities were not detected on cerebrospinal fluid examination. Given the progressive nature of the disease and suspected poor prognosis the dog was euthanized. Histopathological analysis of the brain was consistent with fibrinoid leukodystrophy, also known as Alexander disease. Based on the classification used in humans, this is a description of MRI of a case of type II Alexander disease in veterinary medicine, with characteristics different to other described leukoencephalopathies in dogs.